2013
DOI: 10.4103/0972-0707.114360
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the efficacy of laser fluorescence (DIAGNOdent) to detect demineralization and remineralization of smooth enamel lesions

Abstract: Objective:Early detection of smooth surface lesions is important for appropriate management and monitoring of dental caries. The purpose of this in vitro study was to evaluate the efficacy of laser fluorescence to detect demineralization and remineralization of smooth enamel surfaces.Materials and Methods:In this in vitro study, 132 enamel blocks of semi-impacted human third molars were obtained; artificial caries lesions were induced and they were submitted to the pH-cycling process to create remineralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
(40 reference statements)
1
14
0
3
Order By: Relevance
“…The difference between the two time points demonstrated statistical significance, and showed that NaF mouthwash 0.05% was effective in re-mineralizing tooth enamel. the results of this study are also consistent with the results of the Bahrololoomi et al, study in 2013 investigating toothpaste containing 1450 ppm fluoride using the DIAGNOdent pen 2190 to measure mineralized values [19]. Initial value results were 4.04 ± 2.39; after mineral depletion, 11.38 ± 5.95 and following mineral reclamation, 5.48 ± 2.48.…”
Section: Insupporting
confidence: 90%
“…The difference between the two time points demonstrated statistical significance, and showed that NaF mouthwash 0.05% was effective in re-mineralizing tooth enamel. the results of this study are also consistent with the results of the Bahrololoomi et al, study in 2013 investigating toothpaste containing 1450 ppm fluoride using the DIAGNOdent pen 2190 to measure mineralized values [19]. Initial value results were 4.04 ± 2.39; after mineral depletion, 11.38 ± 5.95 and following mineral reclamation, 5.48 ± 2.48.…”
Section: Insupporting
confidence: 90%
“…There are various other factors which influence the detection of caries by DIAGNOdent like the presence of plaque, calculus, food deposits, toothpaste, prophylaxis paste, and stains which could give false-positive readings. 14…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Bahrololoomi inferred that laser fluorescence is an effective method for detection of demineralization in an in vitro condition, but it was not so efficient in the detection of remineralization. [ 9 ] Based on the studies by Fung,[ 10 ] Patil,[ 11 ] and Vashisht,[ 12 ] who used laser fluorescence to assess remineralization, it was decided upon to use it too as an evaluator for watts selection in this study. The laser fluorescence method picks up fluorescence based on the porosity of the enamel surface.…”
Section: Discussionmentioning
confidence: 99%